The cholera outbreak in Yemen: lessons learned and way forward - Frederik Federspiel; Mohammad Ali (BMC Public Health, 2018)
Abstract The Yemen cholera outbreak has been driven by years of conflict and has now become the largest in epidemiologically recorded history with more than 1.2 million cases since the beginning of the outbreak in April, 2017. In this report we review and discuss the cholera management strategies applied by the major international humanitarian health organizations present in Yemen. We find the response by the organizations examined to have been more focused on case management than on outbreak prevention. Oral Cholera Vaccines (OCVs) were not delivered until nearly 16 months into the outbreak. A recent scale-up of the global OCV stockpile will hopefully allow for rapid mass deployment of the OCV in future humanitarian emergencies. Continuous funding to this stockpile will be crucial to maintain this option for prevention and control of cholera outbreaks. Of equal importance will be the timely recognition of the need for mass OCV deployment and development of more specific, comprehensive and actionable evidence-based frameworks to help guide this decision, however difficult this may be. The outbreak highlights the importance for international humanitarian health organizations to have a continuous discussion about whether and to what extent they should increase their focus on pre-emptively addressing the environmental determinants of communicable diseases in humanitarian emergencies. Strong advocacy from the public health community for peace and the protection of human health, by bringing to attention the public health impacts of armed conflict and keeping the world’s political leaders accountable to their actions, will remain crucial.